PENGARUH KUALITAS PELAYANAN DAN CITRA PERUSAHAAN TERHADAP LOYALITAS PELANGGAN (STUDI KASUS PADA HOTEL RATU MAYANG GARDEN PEKANBARU) - Leri Hardian Saputra; Endang Sutrisna (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
This study aims to determine the influence of service quality and corporate image on customer loyalti in Hotel Ratu Mayang Garden Pekanbaru. The Service quality as a variable (X1), corporate image as a variable (X2) andcustomer loyalty as a variable (Y).The Method in this research is descriptive and quantitative using SPSS 20, where samples were used that guess staying in the hotel Ratu Mayang Garden Pekanbaru with method by accidental sampling with respondens as many 100 people. For determine the number of samples used slovin formula and data collection through questionaires and interviews.Result of analysis using multiple linier regretion, t test and F test so that it can be seen that the service quality variable significant effect on customer loyalty, corporate image variable significant effect on customer loyalty and the service quality variable and corporate image variable significant effect on customer loyalty.Keywords : Service Quality, Corporate Image, and Customer Loyalty